You don't know us negroes and other essays - Hurston, Zora Neale (Amistad, an imprint of HarperCollinsPublishers, 2022)
"One of the most acclaimed artists of the Harlem Renaissance, Zora Neale Hurston was a gifted novelist, playwright, and essayist. Drawn from three decades of her work, this anthology showcases her development as a writer, from her early pieces expounding on the beauty and precision of African American art to some of her final published works, covering the sensational trial of Ruby McCollum, a wealthy Black woman convicted in 1952 for killing a white doctor. Among the selections are Hurston's well-known works such as "How It Feels to be Colored Me" and "My Most Humiliating Jim Crow Experience." The essays in this essential collection are grouped thematically and cover a panoply of topics, including politics, race and gender, and folkloric study from the height of the Harlem Renaissance to the early years of the Civil Rights movement. Demonstrating the breadth of this revered and influential writer's work, You Don't Know Us Negroes and Other Essays is an invaluable chronicle of a writer's development and a window into her world and time"--